Cost-effectiveness analysis of second-generation androgen receptor antagonists for the treatment of metastatic hormone-sensitive prostate cancer - Yang, Yang; Chen, Ya-Qing; Huang, Long-Zhuan; Chen, Yong (Frontiers in Public Health, 2025)
ObjectiveThe combination of second-generation androgen receptor (AR) antagonists with androgen deprivation therapy (ADT) has shown good efficacy and safety in advanced prostate cancer. This study aims to evaluate the cost-effectiveness of three second-generation AR antagonists in the treatment of metastatic hormone-sensitive prostate cancer (mHSPC) in China, providing pharmacoeconomic evidence for clinical drug selection.MethodsA Markov model was constructed based on data from the ARCHES, TITAN, and ARANOTE phase III clinical trials, with a 28-day cycle period. Direct medical costs and quality-adjusted life years (QALYs) were simulated over a 15-year horizon. The incremental cost-effectiveness ratio (ICER) was used as the primary outcome, and a willingness-to-pay (WTP) threshold of three times the 2024 per capita GDP of China was set for cost-utility analysis. Sensitivity analysis was conducted to validate the model’s influencing factors and the robustness of the results.ResultsThe cumulative cost of the apalutamide regimen was ¥776,807, resulting in 4.95 QALYs. Compared to apalutamide, the ICER for enzalutamide was ¥643,309/QALY, while for darolutamide, the ICER was -¥40,625/QALY.ConclusionFor Chinese mHSPC patients, darolutamide is the most cost-effective treatment at a WTP threshold of ¥287,391/QALY, followed by apalutamide, with enzalutamide being less favorable.